EMPOWERMENT OF RURAL CATTLE FARMERS: INTEGRATING SUSTAINABLE PRACTICES AND IMPROVED MARKET ACCESS FOR LIVELIHOOD ENHANCEMENT - Sedana Putra P, Komang Widhya; Maitri, Wayan Sri (Progress In Social Development, 2025)
Community empowerment through micro-enterprise development can be an effective instrument in poverty alleviation. This study will review sustainable farming practice implementation and improved market access with regard to cattle farmers in Klungkung District, Bali, where there exists strong cultural affinity towards natural conservation. This research, using the theory of sustainable development, which links economic, social, and environmental variables, identifies those interventions that would enhance farmers' management capacity and improve market access. The approach adopted in the study is a qualitative one with a descriptive-analytical design, in which purposive sampling is done from 15 cattle farmers and 5 stakeholders who are involved in livestock management. The results showed marked improvements in health management of the livestock, business planning, and marketing strategies after the intervention. Besides, environmentally friendly agricultural practices, such as the use of organic waste as fertilizer, are also adopted. Marketing groups were formed where farmers could sell directly, thus minimizing dependence on intermediaries, enhancing bargaining power, and improving profit margins. The study has pointed out that the active participation of farmers and stakeholders is very crucial for the success of this empowerment program. Longitudinal studies should be conducted to further monitor the sustainability of the program regarding its long-term impact.